Effect of sevoflurane anesthesia on the severity of renal histopathologic changes in rabbits pretreated with gentamicin: A controlled, investigator-blinded, experimental study - Bestas, Azize; Bayar, Mustafa Kemal; Akpolat, Nusret; Okuducu, Mehmet Nihat (Elsevier, 2006)
Background: Inorganic fluoride and compound A are potential nephrotoxic products of sevoflurane, a halogenated inhalational general-anesthetic drug. Objective: The aim of this study was to microscopically examine the effect of sevoflurane on the severity of renal histopathologic changes in rabbits pre-treated with gentamicin. Methods: In this controlled, investigator-blinded, experimental study at the Firat University School of Medicine, Elazig, Turkey, male New Zealand white rabbits (age range, 6-8 months; weight range, 2600-3400 g) were randomly divided into 4 groups of equal size. The gentamicin group received IM gentamicin 10 mg/kg center dot d(-1) for 10 days. Rabbits in the sevoflurane group received pH-balanced saline solution at a volume of 10 mg/kg center dot d(-1) for 10 days, equivalent to the volume of gentamicin administered to the gentamicin group. On day 11, anesthesia was induced with 8% sevoflurane in 50% oxygen and air using a suitable face-mask. When a sufficient depth of anesthesia (loss of eyelash reflex and tolerance to tail-clamp stimuli) was reached (without a muscle relaxant), the rabbits were intubated (3-mm ID) and allowed to breathe spontaneously. End-tidal or end expiratory concentration of sevoflurane was then decreased to 4% and the rabbits were anesthetized at a flow rate of 4 L/min for 4 hours. The rabbits in the gentamicin + sevoflurane group were treated with IM gentamicin at a dosage of 10 mg/kg center dot d(-1) for 10 days. On day 11, they were exposed to sevoflurane, as described for the sevoflurane group. The control group received IM pH-balanced saline solution for the duration of the study. Twenty-four hours after treatment completion, all rabbits were euthanized and kidney tissue samples were obtained. Histopathologic examinations were then carried out using light microscopy. Changes in renal histopathology were based on the percentage of acute tubular necrosis (ATN) and judged on a scale from none to severe. Results: Forty male New Zealand white rabbits (mean [SD] age, 7 [0.49] months; mean [SD] weight, 2900 [150] g) were divided into 4 groups of 10 rabbits each. Proximal renal tubule cell injury in the form of ATN (the mean score) was significantly greater in the 3 treatment groups than in the control group (all, P < 0.001), especially at the corticomedullary junction. In the 3 treatment groups, the most severe renal damage observed was rated as mild (10%-25%). More rabbits in the gentamicin + sevoflurane group had mild renal damage (7) than in the gentamicin group (4) or the sevoflurane group (4), but the between-group differences were not statistically significant. Conclusion: In this experimental study of the effects of sevoflurane on the severity of renal histopathologic changes, a higher percentage of rabbits were observed to have greater renal damage in the gentamicin + sevoflurane group than the other groups. However, between-group differences did not reach statistical significance.
Keywords: nephrotoxicity; sevoflurane; gentamicin; histopathology